(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Meningitis is a serious infection in HIV patients claiming millions of lives across the world. Comparative studies of meningitis in HIV positive and negative patients are scarce. Methods: We studied the comparative clinical profile of a 116 HIV seropositive and 218 HIV seronegative patients with meningitis at a tertiary care hospital in India. Results: High proportion of altered sensorium [84.7% vs. 70.5%], relatively higher median CSF white blood cell count [100 cells/mm3 vs. 35 cells/mm3] and higher median CSF protein content [170 mg/dl vs. 90 mg/dl] were seen in HIV positive patients. Conclusions: Our study shows that meningitis in HIV positive individuals is clinically more severe with more inflammation in the CNS. This can partly explain the high case fatality rates of meningitis in HIV positive patients.